(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This paper sustains the thesis that the symbolic force of Goya’s painting allows us to speak of a thought guided by the referential sustenance of black. In this way, we will emphasise that his entire oeuvre implies the consideration of a profound thought on human existence. In order to develop this objective, we shall enter into a dialogue with the Spanish painter’s work as a whole. Through the analysis of the different stages, it will be possible to corroborate how the common thread of melancholy becomes a hermeneutic key. His melancholic painting will become the energy of the processes of transformation of his painting and of his own biography. The development of the alchemical process of the whole ensemble, through which we witness the progressive existential distillation of the nigredo, will therefore be spontaneously noticed.